PHYTOCHEMICAL EVALUATION, GC-MS ANALYSIS OF PHYTOACTIVE COMPOUNDS, AND ANTIBACTERIAL ACTIVITY STUDIES FROM LINUM USITATISSIMUM - THAMILMARAI SELVI B; SATHAMMAI PRIYA N; STEFFI PF; PRIYADARSHNI S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The flaxseed or linseed (Linum usitatissimum) is a minor oil seed belonging to the family Linaceae and genus Linum, which has been used as a precious nutritional food grain and folklore medicine in human diets for thousands of years and more. Recently, it has been used as a source of nutraceuticals and identified as a healthy component whose benefits on health are generally attributed to the high concentration of linolenic acids (omega 3) and lignans as well as significant quantities of dietary fiber including soluble and insoluble fibers. Methods: The present study was carried out to assess the various phytochemical compositions, Gas chromatogram and Mass spectrometry (GC-MS) analysis, and antibacterial potential of different extracts of L. usitatissimum. Results: The crude extracts of L. usitatissimum revealed the presence of several biologically active phytochemicals with the highest quantity of steroids, terpenoids, flavonoids, tannins, cardiac glycosides, protein, and amino acids. The antibacterial potency was explored against pathogenic bacteria, and the highest inhibitory activity of ethanol and methanol extracts was obtained against Staphylococcus aureus. The GC-MS analysis provides different peaks determining the presence of 10 phytochemical compounds with different therapeutic activities. The phytoactive principles were described with their molecular formula, retention time, molecular weight, and peak area (%). Conclusion: Our results confer the utility of this plant extract in developing novel broad-spectrum therapeutic agent.